The strike in the peruvian labor law - Arévalo Vela, Javier (2022)
This paper presents a review and analysis of legal provisions and jurisprudential criteria, as well as doctrine, on the right to strike in the Peruvian labor regime of private sector. The Single Consolidated Text of the Collective Labor Relations Act is analyzed as the main legal tool. Also, the main aspect of the strike includes seeking to point out its definition, characteristics, essential content, ownership, limits, requirements, among others. Furthermore, the legality and illegality of the strike is defined, the determination of which is issued by a decision of the Administrative Labor Authority.